Il ruolo di TAF12B e UVR3 nel ciclo circadiano dei vegetali - Pollastri, Susanna (Premio Tesi di Dottorato, 2013)
The book goes over the studies carried out on the circadian oscillators in plants, performed using the model plant Arabidopsis thaliana. The plant's oscillators seem to include similar components to those described for other model organisms. A bioinformatic analysis on the Arabidopsis genome found the genes TAF12b, At1g17440 and UVR3, At3g15620. Both the genes were cloned with the GFP green fluorescent protein in order to locate this protein at cell level. Furthermore, Arabidopsis SALK line plants were grown and selected, mutating the genes in question, and in parallel gene expression tests were performed on the main circadian rhythm genes in order to monitor their expression both in conditions of alternating light and dark, and in constant conditions. From the data that has emerged to date it seems that both genes are involved in the Arabidopsis's circadian rhythms.